The work of woman in Aleppo in the 18th.century (Journal of Hama University, 2019)
This research is shedding light on the women's economic and social activities in Aleppo governorate during the eighteenth century AD, depending on the documents of religious courts archived in the building of the historic documents in Damascus and also to the writings of some historians, travelers and physicians who either dwelled in Aleppo city or come over during the period of the eighteenth century. The research has seen that the Aleppian women possessed homes, worked in trade, hired and rented houses. They had also practiced industrial and commercial jobs, had knowledge and educated but on a smaller scale comparing with men. The research has also mentioned that the business of the Aleppian women wasn’t exclusive to a sect or a religion by itself. This is a clear evidence of the religious freedom and equality among people. Furthermore, some businesses were monopolized by women excluding men. The research pointed out the difficulties and obstacles that were created through the women's work inside an illiberal society as the situation was in Aleppo at the time of the research, and how some of these problems were solved by consulting the judge who, in his turn, relied on the beliefs of the Islamic law and the prevailing social ideology and also by contracts and witnesses between the conflicting parties. Regardless of this, it has become clear, by the research, that there weren't handicraft professions related to women although there were one hundred at the time of the research. This proves that the inferior perspective toward the woman is still spreading in the field of the firsthand business. However, this doesn’t put an end to the women's role as a workforce in the Aleppian community.